Pennyworth. The complete first season [videorecording (DVD)] - Cannon, Danny; Cannon, Danny; Eagles, Bill; Bannon, Jack (British actor); Aldridge, Ben; Bennett, Hainsley Lloyd; Kane, Bob; Finger, Bill, 1914-1974 (Warner Bros. Entertainment, 2020)
Follows the adventures of former British SAS soldier Alfred Pennyworth as he forms his own security company and begins working against the Raven Society with Thomas Wayne and Martha Kane, the future parents of Bruce Wayne/Batman.